PENYULUHAN MANAJEMEN PEMASARAN BISNIS SYARIAH EKONOMI KREATIF DI MASA PANDEMI COVID-19 DI DESA CIBITUNG KULON, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Susi Melinasari; Hasbi Ash Shiddieqy; Nursela Agustina Indriyani (SAHID EMPOWERMENT JOURNAL, 2023)
Corona Virus or what we know as Covid-19 is a topic of discussion in Indonesia. Of the several sectors affected by Covid-19, the economic sector in the business sector is the sector most affected because many small and medium companies have had to lay off their employees due to decreased income due to their products not selling smoothly and stopping. In this case, the community service program implemented in Cibitung Kulon Village, Pamijahan District, Bogor Regency is marketing outreach on creative economy sharia business management supported by the use of social media which can be easily accessed anytime and anywhere. This is because most of them post advertisements on social media such as Facebook, Instagram, Whatsapp, and even the Tiktok application. The ease and speed of placing advertisements makes online businesses in the midst of the current pandemic liked by most people.